Model Inovasi Kolaboratif dalam Implementasi Program Open Data: Tantangan dan Manfaatnya bagi Publik - Anne Friday Safaria; Ida Widianingsih; Entang Adhy Muhtar; Ira Irawati (Universitas Medan Area, 2019)
Open Data (OD) is data that is publicly available and free for anyone to use, reuse and redistribute. The Bandung City Government is the first municipality government in Indonesia to implement OD programs as a form of public service in the digital era. Although E-government practices have been applied to public services provided by various Central and Regional government agencies in Indonesia, in general there are still obstacles related to the extent to which the data can be accessed and used-reused by the public for various purposes. The study conducted in the Bandung Municipality Government was directed at efforts to find an effective OD innovation management model in the public sector by using qualitative methods with a case study strategy. Based on field findings, the OD program carried out at the Bandung Government is a collaboration of multiple actors and stakeholders (communities, private sector, NGOs) starting from the initiation stage up to its implementation. In this case, the Bandung City Government together with the various parties involved built an Open Data ecosystem that aims to produce credible data for decision making, and create a more transparent and accountable government. The implementation of this program has not been fully effective because the implementation has not been optimally integrated in Public Information Services (LIP). This has implications for the mechanism of unclear and non-smooth coordination and communication between fields and between Regional Government Work Units (SKPD) which are responsible for implementing OD and LIP. The stuation raises different views on the selection and display of data published (information dissemination).